2023
DOI: 10.1111/febs.16696
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan alleviates sepsis‐induced acute lung injury via inhibiting GSDMD‐dependent macrophage pyroptosis in mice

Abstract: Sepsis-induced acute lung injury (ALI) is a life-threatening disorder with intricate pathogenesis. Macrophage pyroptosis reportedly plays a vital role in ALI. Although it has been established that angiotensin receptor blockers (ARBs) can reduce sepsis-induced organ injury, the efficacy of sacubitril/valsartan (SV) for sepsis has been largely understudied. Here, we aimed to investigate the role of SV in sepsis-induced ALI. Caecal ligation and puncture (CLP) were used to induce polymicrobial sepsis and related A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…A similar study using a dual inhibitor of neprilysin and ACE on septic mice found consistent results, including decreased levels of pro-inflammatory cytokines and evidence of lung protection on histology [82]. Similar findings were seen using Sacubitril/valsartan, a dual inhibitor of neprilysin, and an ARB [83]. The inhibition of the RAAS, whether by gene knockout or the use of an antagonist, demonstrated improvements in several organs, including the heart, spleen, and lungs, and improved overall survival.…”
Section: Impact Of Raas Inhibitors On Risk For S-akisupporting
confidence: 59%
See 1 more Smart Citation
“…A similar study using a dual inhibitor of neprilysin and ACE on septic mice found consistent results, including decreased levels of pro-inflammatory cytokines and evidence of lung protection on histology [82]. Similar findings were seen using Sacubitril/valsartan, a dual inhibitor of neprilysin, and an ARB [83]. The inhibition of the RAAS, whether by gene knockout or the use of an antagonist, demonstrated improvements in several organs, including the heart, spleen, and lungs, and improved overall survival.…”
Section: Impact Of Raas Inhibitors On Risk For S-akisupporting
confidence: 59%
“…The use of RAAS antagonists as a therapeutic option in sepsis has recently been considered, with emerging studies that help form a greater understanding of the role of RAAS inhibitors in sepsis. Several studies observed decreased rates of S-AKI, renal tissue damage, and levels of pro-inflammatory cytokines and oxidative stress with the use of RAAS antagonists as treatment during sepsis [84][85][86], as well as evidence of their playing a protective role in other organs, including the lung [81][82][83], heart [78][79][80], and spleen [79]. RAAS inhibitors modulate the activity of angiotensin II and minimize its downstream effects on inflammation and coagulation.…”
Section: Impact Of Raas Inhibitors On Risk For S-akimentioning
confidence: 99%